Morphological and molecular characterization of Labronema montanum sp. n. (Dorylaimida, Dorylaimidae) from Spain - Peña-Santiago, R. (J Nematol, 2019)
A new species of the genus Labronema, collected in a natural mountain habitat of the southern Iberian Peninsula, in Spain, is studied, including its morphological and morphometric characterization, SEM observations, and D2-D3 28S-rRNA sequences. Labronema montanum sp. n. is distinguishable by its 1.56 to 2.08 mm long body, with lip region being offset by constriction and 19 to 24 µm broad, odontostyle 21 to 29 µm long, neck 417 to 551 µm long, pharyngeal expansion 205 to 272 µm long, the presence of three cardiac lobes at the pharyngo-intestinal junction, a long and tripartite uterus, longitudinal vulva (V = 57-60), a short and rounded caudal region (19–35 µm, c = 56-86, c = 0.5-0.8), spicules 65 to 76 µm long, and 20 to 25 nearly contiguous ventromedian supplements with hiatus.